ANALISIS GAYA KEPEMIMPINAN DEMOKRATIS GURU TERHADAP PENINGKATAN PRESTASI AKADEMIK DAN NON AKADEMIK KELAS 1 SDN BURENGAN 2 KOTA KEDIRI - Farihat, Khoshishti Shofin (Jurnal Dikdas Bantara, 2023)
Analysis of the teacher's democratic leadership style on student achievement and behavior patterns at SDN Burengan 2, Kediri City, is important. The aim of this research is the analysis of the teacher's democratic leadership style on increasing academic and non-academic achievement for class 1 of SDN Burengan 2, Kediri city. A method is a method used to solve the problem of an object being studied. The research method/approach used in this research is a descriptive qualitative approach. By providing freedom in decision making, students are stimulated. creative thinking and better problem solving. The research results show that it has an impact on students' academic and non-academic achievements, where they can apply critical thinking and creativity in solving problems and completing complex tasks.